PROMISCUITY IN EKA KURNIAWAN’S NOVEL LELAKI HARIMAU - Nurlaili, Nurlaili; Chairani, Sri; Purwarno, Purwarno; Manugeren, M. (JOURNAL OF LANGUAGE, 2024)
Promiscuity, a recurring theme in literature, is examined through various lenses, reflecting the complexities of human relationships, societal norms, and cultural contexts. In Eka Kurniawan's novel Lelaki Harimau, promiscuity serves as a thematic lens through which Kurniawan explores the intricate interplay of desire, power, and societal expectations. This paper aims to delve into the portrayal of promiscuity in Lelaki Harimau, employing a sociology of literature approach combined with a qualitative descriptive method. Through close textual analysis and thematic exploration, the study seeks to unravel the cultural, social, and psychological dimensions of promiscuity as depicted in the novel. The research findings highlight the destructive consequences of unchecked hedonism, as exemplified by characters like Anwar Sadat and his daughter Laila. Furthermore, the study discusses how Kurniawan's narrative challenges entrenched notions of morality and sexuality, urging readers to confront uncomfortable truths about human nature and societal constructs. Ultimately, Lelaki Harimau emerges not only as a compelling work of literature but also as a powerful commentary on the enduring relevance of literature in illuminating social issues and advocating for positive change.